Terpinen-4-ol, the Main Bioactive Component of Tea Tree Oil, as an Innovative Antimicrobial Agent against Legionella pneumophila - Mondello, Francesca; Fontana, Stefano; Scaturro, Maria; Girolamo, Antonietta; Colone, Marisa; Stringaro, Annarita; Vito, Maura Di; Ricci, Maria Luisa (Pathogens (Basel), 2022)
Legionella pneumophila (Lp), responsible for a severe pneumonia called Legionnaires’ disease, represents an important health burden in Europe. Prevention and control of Lp contamination in warm water systems is still a great challenge often due to the failure in disinfection procedures. The aim of this study was to evaluate the in vitro activity of Terpinen-4-ol (T-4-ol) as potential agent for Lp control, in comparison with the essential oil of Melaleuca alternifolia (tea tree) (TTO. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of T-4-ol were determined by broth micro-dilution and a micro-atmosphere diffusion method to investigate the anti-Lp effects of T-4-ol and TTO vapors. Scanning Electron Microscopy (SEM) was adopted to highlight the morphological changes and Lp damage following T-4-ol and TTO treatments. The greatest antimicrobial activity against Lp was shown by T-4-ol with a MIC range of 0.06–0.125% v/v and MBC range of 0.25–0.5% v/v. The TTO and T-4-ol MIC and MBC decreased with increasing temperature (36 °C to 45 ± 1 °C), and temperature also significantly influenced the efficacy of TTO and T-4-ol vapors. The time-killing assay showed an exponential trend of T-4-ol bactericidal activity at 0.5% v/v against Lp. SEM observations revealed a concentration- and temperature- dependent effect of T-4-ol and TTO on cell surface morphology with alterations. These findings suggest that T-4-ol is active against Lp and further studies may address the potential effectiveness of T-4-ol for control of water systems.